Description and outcomes of patients with substance use disorder with serious bacterial infections who had a multidisciplinary care conference. (August 2022) - Conte, Michael; Schneider, Brent; Varley, Cara D.; Streifel, Amber C.; Sikka, Monica K.
Background: Patients with substance use disorders (SUDs) and severe bacterial infections requiring prolonged antibiotic therapy represent a significant challenge to providers due to complexity of care coordination required to ensure safe and effective treatment. Our institution developed a patient-centered multidisciplinary discharge planning conference, OPTIONS-DC, to address this challenge. Methods: We conducted a retrospective review to evaluates parameters between patients who received an OPTIONS-DC and those who did not. Results: We identified 73 patients receiving an OPTIONS-DC and 100 who did not. More patients with an OPTIONS-DC were < 40 years of age (76.7% versus 61.0%, OR = 2.3, 95% CI = 1.1–4.7, p  = 0.02), had positive HCV antibody testing (58.9% versus 41.0%, OR = 2.1, 95% CI = 1.1–3.8, p  = 0.02), injection drug use (93.2% versus 79.0%, OR = 3.6 95% CI = 1.3–10.1, p  = 0.01), used methamphetamines (84.9% versus 72.0%, OR = 2.2, 95% CI = 1.0–4.8, p  = 0.04), and started inpatient SUD treatment (80.8% versus 63%, OR = 2.5, 95% CI = 1.2–5.0, p  = 0.04) compared with those without a conference. The OPTIONS-DC group was more likely to be diagnosed with bacteremia (74.0% versus 57.0%, OR = 2.1, 95% CI = 1.1–4.1, p  = 0.02), endocarditis (39.7% versus 21.0%, OR = 2.5, 95% CI = 1.3–4.9, p  = 0.03), vertebral osteomyelitis (45.2% versus 15.0%, OR = 4.7, 95% CI = 2.3–9.6, p  < 0.01), and epidural abscess (35.6% versus 10.0%, OR = 5.0, 95% CI = 2.2–11.2, p  < 0.01) and require 4 weeks or more of antibiotic treatment (97.3% versus 51.1%, OR = 34.1, 95% CI = 7.9–146.7, p  = 0.01). Patients with an OPTIONS-DC were also more likely to be admitted between 2019 and 2020 than between 2018 and 2019 (OR = 4.1, 95% CI = 2.1–7.9, p  < 0.01). Conclusion: Patients with an OPTIONS-DC tended to have more complicated infections and longer courses of antibiotic treatment. While further research on outcomes is needed, patients receiving an OPTIONS-DC were able to successfully complete antibiotic courses across a variety of settings.